A Semiotic Analysis on Atlas Beach Club Advertisement in Canggu - Toti, I Putu Mario Bintang; Laba, I Nengah; Sutrisna, Km. Tri (LPPM Universitas Dhyana Pura, 2024)
This study aims to identify the denotation, connotation, and myth meaning in Atlas beach club advertisement. This study used the theory of Roland Barthes Semiotic (1988). He stated there are two layers of sign meaning the first layer is denotation meaning and the second layer is connotation meaning. Denotation is the real meaning then connotation is the meaning that related with culture or language users and can become myths. The qualitative method was used in this study where the data was taken from the content on the flyers of Atlas Beach Club using documentation and note-taking technique. The analysis showed that the contents of the flyers from Atlas Beach Club, there were: in the first flyer there are 6 signs such as color, logo, picture, text, table and symbol.